Organ-specific bleeding patterns of anticoagulant therapy: lessons from clinical trials - Vanassche, Thomas; Hirsh, Jack; Eikelboom, John W.; Ginsberg, Jeffrey S. (Thrombosis and Haemostasis, 2014)
Anticoagulants are effective at preventing and treating thrombosis, but can cause bleeding. For decades, vitamin K antagonists (VKAs) have been the only available oral anticoagulants. The development of non-VKA oral anticoagulants (NOACs), which inhibit either factor Xa or thrombin stoichiometrically, has provided alternatives to VKAs for several indications. The results of recent large-scale randomised controlled trials comparing NOACs with VKAs for the prevention of stroke in patients with non-valvular atrial fibrillation (AF) have produced some unexpected results. As a group, NOACs showed similar efficacy as warfarin, but a reduced risk of major bleeding. The reduction in bleeding with NOACs was greatest with intracranial hemorrhage. In contrast, the relative risk of gastro-intestinal bleeding was increased with some NOACs. In this review, we explore the potential mechanisms as well as the implications of these organ-specific bleeding patterns.
Keywords: Venous thrombosis; stroke prevention; thrombosis